Biotransformation of Domestic Wastewater Treatment Plant Sludge by Two-Stage Integrated Processes -Lsb & Ssb - Md. Zahangir Alam, A. H. Molla and A. Fakhru’l-Razi (International Islamic University Malaysia Engineering Journal, 2012)
The study of biotransformation of domestic wastewater treatment plant (DWTP) sludge was conducted in laboratory-scale by two-stage integrated process i.e. liquid state bioconversion (LSB) and solid state bioconversion (SSB) processes. The liquid wastewater sludge [4% w/w of total suspended solids (TSS)] was treated by mixed filamentous fungi Penicillium corylophilum and Aspergillus niger, isolated, screened and mixed cultured in terms of their higher biodegradation potential to wastewater sludge. The biosolids was increased to about 10% w/w. Conversely, the soluble [i.e. Total dissolve solid (TDS)] and insoluble substances (TSS) in treated supernatant were decreased effectively in the LSB process. In the developed LSB process, 93.8 g kg-1of biosolids were enriched with fungal biomass protein and nutrients (NPK), and 98.8% of TSS, 98.2% of TDS, 97.3% of turbidity, 80.2% of soluble protein, 98.8% of reducing sugar and 92.7% of chemical oxygen demand (COD) in treated sludge supernatant were removed after 8 days of treatment. Specific resistance to filtration (1.39x1012 m/kg) was decreased tremendously by the microbial treatment of DWTP sludge after 6 days of fermentation. The treated biosolids in DWTP sludge was considered as pretreated resource materials for composting and converted into compost by SSB process. The SSB process was evaluated for composting by monitoring the microbial growth and its subsequent roles in biodegradation in composting bin (CB). The process was conducted using two mixed fungal cultures, Trichoderma harzianum with Phanerochaete chrysosporium 2094 and (T/P) and T. harzianum and Mucor hiemalis (T/M); and two bulking materials, sawdust (SD) and rice straw (RS). The most encouraging results of microbial growth and subsequent solid state bioconversion were exhibited in the RS than the SD. Significant decrease of the C/N ratio and germination index (GI) were attained as well as the higher value of glucosamine was exhibited in compost; which clearly implied that the increased bioconversion occurred in the treated process. Comparatively, superior composts were produced by T/P at 50-60 days of SSB. Significantly lower heavy metals (Pb, Cd, Cr, Ni, Cu and Zn) were recorded in chemical analysis of the end products (composts) after SSB, in comparison to the USA’s recognized limits for application in municipal solid waste (MSW). Keywords: Liquid state bioconversion, solid state bioconversion, domestic wastewater sludge, filamentous fungi, biosolids and compost.